(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores how Meena Kandasamy reclaims space for marginalized voices—particularly Dalit women—through selected poems from her collections Touch and Ms. Militancy. Drawing on both personal and collective histories, Kandasamy rewrites myth, history, and language to challenge dominant narratives of caste and gender in Indian society. Her poetry speaks from a place of defiance, using irony, anger, and tenderness to confront deeply rooted systems of oppression. The study also reflects on how Kandasamy manipulates language itself—as both a tool of exclusion and a potential means of liberation. By reshaping English to reflect her cultural and political reality, Kandasamy transforms poetry into a form of resistance, making space for identities often erased or silenced in mainstream discourse.